Self-Disclosure and Post-traumatic Growth in Korean Adults: A Multiple Mediating Model of Deliberate Rumination, Positive Social Responses, and Meaning of Life - Ryu, Ji-Hyun; Suh, Kyung-Hyun (Frontiers in Psychology, 2022)
Background: To explore how self-disclosure leads to post-traumatic growth (PTG) in adults who have experienced traumatic events, this study identified the relationship between self-disclosure and post-traumatic growth in Korean adults. We examined a parallel multiple mediating model for this relationship. Methods: Participants were 318 Korean male and female adult participants aged 20 years or older who had experienced trauma. We measured deliberate rumination, positive social responses, and the meaning of life as mediating variables. Results: The results revealed that the study variables positively correlated with PTG. Self-disclosure was positively correlated with deliberate rumination, positive social responses, and meaning of life. In the multiple mediating model, deliberate rumination, positive social responses, and meaning of life mediated the relationship between self-disclosure and PTG. Conclusion: Self-disclosure, deliberate rumination, positive social responses, and meaning of life play an important role in the growth of adults who have experienced traumatic events. The findings of this study should provide valuable information for future research and for mental health professionals who want to promote the PTG of their clients.